Relationships between personality, fear and depression in patients with breast cancer - Stankiewicz, Arkadiusz; Radziwiłłowicz, Wioletta; Bidzan, Mariola (Psychoonkologia, 2011)
Presented paper discovers relations between psychological features – personality, fear and depression – and time from cancer diagnosis. Participants were 30 women with breast cancer. Half of the sample is the beginner group (at the start of therapy) and the second half is the group after 5 years of therapy. Results suggest there are no significant differences in means in many of analysed features, but very interested significant differences were found in correlations between personality features and fear or depression in both groups. Mechanism of fear and (less significant) depression building is strongly related to neurotism, agreeability and conscientiousness in patient after 5 years of therapy than patients at the beginning.